The Free Press in Indonesia as Human Security?: A Preliminary Analysis - Ali Maksum (Andalas Journal of International Studies (AJIS))
This paper discusses human security in the context of media threat towards the society in Indonesia. Specifically this paper seeks to explain the development of media liberalization in Indonesia and the impact on civil rights in obtaining the truth information and the quest for true and reliable information. The increasing number of top businessmen owning media companies, following political and economic liberalization has been one of the most important phenomena over the past few years. The acquisition of media companies by businessman and politicians will influence indirectly the content of news reports. Finally, some radical groups have taken advantage of the free press policy to infiltrate Indonesian moderate Muslim society. Overall, media have failed to show their responsibility and seem to be far from the ethics because they are owned by businessmen, politicians and interest groups.